THE MALAYSIA-SINGAPORE SEPARATION IMPACT TO MALAYSIA’S NATIONAL SECURITY - Fatimah Kuzi; Bushrah Basiron, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
The 1965 separation of Malaysia and Singapore was a crucial event in the history of Southeast Asia, greatly impacting Malaysia's national security situation. This article examines the continuous threats and long-term effects of the separation on Malaysia's national security apparatus. Singapore's separation from Malaysia was influenced by several factors, including profound political ideology, economic gaps, and racial conflicts. As a result, Malaysia had to traverse a challenging regional landscape characterized by the Cold War, communist insurgencies, and power dynamics among neighbouring countries. Following the immediate aftermath, Malaysia's task was to reaffirm authority and stability within its recently delineated boundaries. Malaysia's national security strategy has evolved, with a focus on enhancing its defence infrastructure, fortifying bilateral relationships with neighbouring nations, and actively participating in international alliances. This article employs a qualitative approach to elucidate the threats between Malaysia and Singapore, utilizing NVivo 12 software for data analysis. It concludes by highlighting the significance and relevancy of the Malaysia-Singapore separation, as well as the existence of new threats between both states.